Record documentation of AFTO 781 series in the aspect of safety of operation of F-16 aircraft at Poznan - Krzesiny airport. Analysis of experience in 2010 - 2020 - Geppert Karol (2023)
The purpose of the article is to present the conclusions and discuss the results of research outcome from the implementation and use of AFTO 781 record documentation in the formation of safety in the process of operation of a multirole aircraft F-16 C/D Block 52+ at Poznan - Krzesiny Airport in 2010 - 2020.